Economic crisis and mental health – findings from Greece - Christodoulou, N. (Die Psychiatrie, 2017)
Background: The direct and indirect effects of the economic crisis in Greece have resulted in inequalities, poverty and unemployment. Public health services, social care and welfare have been both severely curtailed and overstretched by increased demand due to higher private care costs and the refugee crisis. For society’s most vulnerable this is beyond an economic crisis, it is a humanitarian crisis. Method: In this narrative review we report a continued rise in suicides, persistent mental health problems in the population, and continued systemic problems despite some successful reforms and slowing of the economic deterioration. Synergistic effects are identified between pre-existing systemic weaknesses, the effects of the crisis, and the effects of austerity. Outlook: Psychiatrists should promote evidence- based interventions, for example preventing mental illness by supporting vulnerable groups and by reducing inequalities. Evidence-based heurism is advocated for, in the interest of outcome. Psychiatrists also have a political role in tackling stigma towards mental illness, refugees and other vulnerable groups, and in promoting resilience and solidarity.
Keywords: Economic crisis; Greece; psychiatry; suicide; mental health services; refugee crisis